1990
DOI: 10.4039/ent1221111-11
|View full text |Cite
|
Sign up to set email alerts
|

FEEDING PREFERENCES OF THE WESTERN FLOWER THRIPS, FRANKLINIELLA OCCIDENTALIS (PERGANDE) (THYSANOPTERA: THRIPIDAE), AND INCIDENCE OF TOMATO SPOTTED WILT VIRUS AMONG CULTIVARS OF FLORIST’S CHRYSANTHEMUM

Abstract: A wide range in feeding damage as defined by leaf scars among 27 cultivars of florist’s chrysanthemum was apparent for the western flower thrips, Frankliniella occidentalis (Pergande). Assessments based on numbers of feeding scars or ranking of cultivars on the basis of the leaf area damaged by feeding were in close agreement. Cultivars with the most feeding damage under growth room conditions, such as cvs. White Marble and Polaris, were the same as those in plots within a naturally infested commercial greenho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0
9

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 20 publications
3
9
0
9
Order By: Relevance
“…In chrysanthemum, large genetic variation in thrips resistance was shown for all measured parameters. This corresponds to the results of other authors, who found the same range of variation in 'silver' damage among chrysanthemum cultivars (Broadbent et al, 1990;van Dijken, 1992). In spite of a high thrips pressure during ten weeks, plants without any feeding damage were present.…”
Section: Discussionsupporting
confidence: 91%
“…In chrysanthemum, large genetic variation in thrips resistance was shown for all measured parameters. This corresponds to the results of other authors, who found the same range of variation in 'silver' damage among chrysanthemum cultivars (Broadbent et al, 1990;van Dijken, 1992). In spite of a high thrips pressure during ten weeks, plants without any feeding damage were present.…”
Section: Discussionsupporting
confidence: 91%
“…These results stressed the importance of tomato plants as potential sources for newly infected thrips, and suggested that the removal of the TSWVinfected plants in a crop could have positive effects in the general control of the disease. Similar differences in transmission efficiencies of TSWV isolates due to acquisition host species have been reported for other hosts (Broadbent et al, 1990;Ullman et al, 1992b;Wijkamp et al, 1995) and have been related to the differential distribution of TSWV in host tissues (German et al, 1992) or to differential feeding preferences of the thrips (Lewis, 1973). Although it has been suggested that TSWV can cause pathological effects on WFT (Robb, 1989), it should be emphasized that the transmission data compared in this paper were not biased by possible deleterious effects of TSWV in the thrips.…”
Section: Discussionmentioning
confidence: 56%
“…Transmission of TSWV by T. tabaci also seems to be affected by the host on which the virus is acquired. Effects of the acquisition host on transmission have been observed in many studies (Sakimura, 1939;Broadbent et al, 1990;Roca et al, 1997). Acquisition from D. stramonium resulted in better transmission than that from E. sonchifolia, although the second species has been reported as a good virus source for T. tabaci (Sakimura, 1963) and F. occidentalis (Bautiste et al, 1995).…”
Section: Discussionmentioning
confidence: 98%